Solidaritas Pa’Taksi di Desa Tetewatu Kecamatan Lilirilau Kabupaten Soppeng - Idham Irwansyah; Mario Mario; Zulham Wijaya (Seminar Nasional LP2M UNM, 2019)
Abstract. This research aims to know (1) Form of solidarity Pa’'Taksi in the village Tetewatu Lilirilau District of Soppeng District (2) factors that encourage and (3) factors that impede the solidarity Pa 'Taksi in the village Tetewatu District Lilirilau District Soppeng.The type of research used is a qualitative descriptive that illustrates how the solidarity relationship of fellow Pa'Taksi in the village Tetewatu District Lilirilau subdistrict Soppeng. The technique of determining the informant using the purposive sampling technique by selecting an informant of 8 people as Pa'Taksi to facilitate researchers in obtaining information.The results of the study showed that the solidarity form of fellow Pa'taksi in the village of Tetewatu district of the district of Soppeng is a mechanical solidarity, it is seen from the collective work of mutual mutually and embedded flavors Empathy among them. The close relationship between them is also based on the norm and customs prevailing in the local village. The factors that promote solidarity are the common moral responsibilities, and the intensity of meetings between them. While the inhibitory factor is an understanding of common ideals, economic factors and a different psychic and psychological factors Keywords: Solidrity, Pa’Taksi